Facility Layout Redesign Using Systematic Layout Planning Method in Pt. Pilar Kekar Plasindo - Suhardi, Bambang; Elvira, Lulu; Astuti, Rahmaniyah Dwi (UUM Press, 2021)
Good equipment and product design are meaningless if there is no good layout planning. Problems owned by PT. Pilar Kekar Plasindo occurs in the production of small polyethylene. This is because small polyethylene production has large material total transfer distance. Small polyethylene problems include the distance between stations, cross-movement, backtracking, and the broken machine that is still placed in the production section. These conditions make the material handling costs and distance large. Therefore, this research aims to produce a layout design of production facilities that can minimize the distance and cost of material movement. The method used in this study is Systematic Layout Planning (SLP). Three alternative designs were compared, and the second proposed facility layout was chosen because it can reduce the total cost of material transfer by 68.3% and reduce the distance of material transfer by 59.6% from the initial facility layout.